Studies on the chemistry of diazadiborinines - Goh, Gillian Kor Hwee (Nanyang Technological University, 2021)
Transition metal catalysts had long been well known for its generation of toxic side products in many reactions. In addition, transition metal catalysts are often expensive, increasing the disadvantages of the utilization of such catalysts. At such, many researchers had since turned their focus on to utilizing main group catalysts which promotes a greener and lower cost alternative. Among various classes of the main group catalysts, most research had been completed on Phosphorous, Germanium, Silicon, Aluminum compounds as well as azaborinines. However, the scope of diazadiborinines successfully synthesized remained limited to date. As such, the reported catalytic ability of diazadiborinines remained scarce. Nevertheless, previously reported catalytic activity of diazadiborinines had displayed vast potential to be investigated based on its prior ability to activate many small molecules including enthalpically strong -bonds as well as non-activated unsaturated bonds with mild reaction conditions. With that, we are interested to pursue the novel chemistry of diazadiborinines in this thesis. We attempt to synthesize new diazadiborinines with more efficient reaction pathways and explore unprecedented reactivity as well as to understand the mechanism of these catalytic systems. This thesis will focus mainly on the utilization of the novel 1,4,2,5 diazadiborinine as an efficient catalyst in C-H bonds and dichalcogenide Se-Se bond activation reactions. The novel chemical transformation of the skeletal isomerization process observed experimentally will also be analyzed. All mechanisms proposed in this thesis were investigated using experimental and DFT calculations. Understanding these catalytic systems and their ability to perform chemical transformations will allow the development of a platform to generate more effective and green catalysts of practical applications in the future.